Jak poznałem Pałac Kultury albo mała refleksja nad twórczością Tadeusza Konwickiego (1926–2015) - Káša, Peter (Postscriptum Polonistyczne, 2020)
The author presents the stories of Central European intellectuals under a communist regime. He interprets one of the greatest novels written by Tadeusz Konwicki, Mała apokalipsa. He concentrates on the portrayal of both grotesque and antiCommunist gestures, a topos of the Communist Warsaw and its strange characters.